Studies in Islamic legal theory - Weiss, Bernard G. (Studies in Islamic law and society, 2002)
This volume is a collection of studies devoted entirely to topics and issues in the field of Islamic legal theory and authored by 14 scholars known for their work in this field. The studies deal with such topics as early notions of charismatic authority.